1998
DOI: 10.1046/j.1471-4159.1998.70041764.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p38MAPK in Microglia After Ischemia

Abstract: p38 MAPK has been implicated in the regulation of promflammatory cytokines and apoptosis in vitro. To understand its role in neurodegeneration, we determined the time course and localization of the dually phosphorylated active form of p38 MAPK in hippocampus after global forebrain ischemia. Phosphorylated p38 MAPK and mitogen-activated protein kinase-activated protein 2 activity increased over 4 days after ischemia. Phosphorylated p38 MAPK immunoreactivity was observed in microglia in regions adjacent to, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(89 citation statements)
references
References 17 publications
7
81
1
Order By: Relevance
“…25 The late appearance of mediators from AA oxygenation could be related to the postischemic inflammatory response after global cerebral ischemia. 26 Alternatively, reperfusion-associated oxidation of phospholipids could produce their modified forms that might be metabolized by Ca 2+ -independent phospholipases, for example by iPLA 2γ in mitochondria. A specific feature of this pathway may be its selectivity toward a peroxidizable and subsequently hydrolyzable phospholipid substrate, a unique phospholipid of mitochondria, CL.…”
Section: Discussionmentioning
confidence: 99%
“…25 The late appearance of mediators from AA oxygenation could be related to the postischemic inflammatory response after global cerebral ischemia. 26 Alternatively, reperfusion-associated oxidation of phospholipids could produce their modified forms that might be metabolized by Ca 2+ -independent phospholipases, for example by iPLA 2γ in mitochondria. A specific feature of this pathway may be its selectivity toward a peroxidizable and subsequently hydrolyzable phospholipid substrate, a unique phospholipid of mitochondria, CL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that the p38 MAPK pathway is activated after hypoxia/ischemia in brain tissue (Walton et al, 1998;. However, there is evidence that p38 MAPK activity is deleterious, mediating the cell death induced by hypoxia (Y. , oxygen glucose deprivation, magnesium withdrawal, and glutamate receptor agonist exposure (Legos et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…p38 MAPK promotes the stabilization and enhanced translation of mRNAs encoding proinflammatory proteins. 147 Activated (phosphorylated) p38 has been demonstrated in microglia in animal models of brain ischemia, 146,148,149 and pharmacological inhibition of p38 with the compound SD-282 decreased the number of activated microglia in ischemic brain. 150 The MAPK/ ERK signaling pathway may also regulate inflammation through its effects on PARP-1 activation, which (as detailed later in this review) is an important modulator of proinflammatory gene expression.…”
Section: Mitogen-activated Protein Kinase (Mapk) Cascadementioning
confidence: 99%